KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG - Hanifah (2022)
This study aims to determine and analyze the effect of celebrity endorser, product quality and perceived ease of use on Samsung smartphone purchasing decisions. This research method uses quantitative methods. The sample used was 75 respondents from Samsung smartphone consumers in South Jakarta with a non-probability sampling technique using the purposive sampling method. Data was collected through a questionnaire with a google form. The data analysis technique used is descriptive data analysis and inferential data analysis with the SmartPLS 3.0 test tool. The results showed that (1) The celebrity endorser variable had a positive and significant effect on purchasing decisions of 0.273, (2) The product quality variable had a positive and significant effect on purchasing decisions of 0.428, (3) The perceived ease of use variable had a positive and significant effect on purchasing decisions of 0.267. Based on the R-Square Adjusted value, it can be explained that celebrity endorser, product quality and perceived ease of use affect purchasing decisions by 79.4% and the remaining 20.6% is influenced by other independent variables not included in this study.